Primary and Secondary English Slang in SCREAM VI Movie: A Sociolinguistics Analysis - Fadhil, Mohamad; Wijaya, Beni; Zakaria (The Study Program of English Education of Palangka Raya University, 2025)
This research analyzed the English slang in the SCREAM VI movie through a sociolinguistic framework focusing on Chapman's primary and secondary slang. Teenage characters for group identity widely use primary slang while secondary slang conveys attitudes and serves as a covert code. The qualitative descriptive method reveals that slang in SCREAM VI creates informality, expresses rebellion, and provides in-group exclusivity. The researchers collected the data by watching the film SCREAM VI, downloading the movie script, and extracting the slang words used in it. The findings highlight the dynamic role of slang in reflecting social dimensions and cultural values within youth subcultures towards the primary and secondary slang found. It is expected that future research explores slang across different media and cultural contexts to further understand its evolution and functions.